Peran Perbankan dalam pemberantasan tindak pidana pencucian uang - Aji, Satria Giras Mukti; Kurnia, Heri (CV. Kurnia Grup, 2024)
Money laundering crimes are rife in Indonesia with banks as the means. Weaknesses in the banking system provide opportunities for money launderers to carry out their actions so that the proceeds of crime obtained are safely stored in the bank. This scientific work research is normative legal research that is descriptive analysis, with a statutory and conceptual approach with a case approach. The purpose of this paper is to analyze the role of banking in efforts to prevent and eradicate money laundering crimes committed by customers from the perspective of banking law and the modes used by perpetrators of money laundering crimes in banks. The results of this research show that the mode used by perpetrators of money laundering crimes in laundering money in banks is through capital cooperation through credit collateral, transfers abroad, disguising domestic businesses, engineering foreign loans and the role of banks in efforts to prevention and eradication of money laundering crimes and banking laws is by identifying prospective customers who will open an account at the bank and monitoring customer profiles and transactions carried out on an ongoing basis, including conformity between transaction profiles and customer profiles, examining similarities or similar names with the name of the suspect/ defendant published in the mass media or by the competent authorities.